The relationship between hysterectomy, menopause, and tubal ligation, with coronary heart diseases in North of Iran: a population-based case–control study - Mehran Asadi-Aliabadi; Mahmood Moosazadeh; Kiarash Shakeriastani; Mohammadmehdi Pejman; Mobina Gheibi; Maliheh Ghasemi Tirtashi; Erfan Ghadirzadeh (Scientific Reports)
Abstract Previously, menopause, hysterectomy, and tubal ligation (TL) have been evaluated as coronary heart disease (CHD) risk factors. However, the results regarding the significance of these associations were conflicting. Thus, the present study aimed to assess whether hysterectomy, menopause, and TL increase the odds of CHD. This case-control study included data from the enrollment phase of the Tabari cohort study (TCS) consisting of 564 cases of CHD and 564 healthy controls. Logistic regression was used to calculate the odds ratio (OR) of CHD in relation to hysterectomy, menopause, and TL status after adjustment for confounders. The univariate logistic regression analysis showed a significantly higher odds of CHD among post-menopausal participants (OR: 5.09, 95%CI 3.92–6.61), participants with TL (OR: 1.81, 95%CI 1.41–2.32), and women with hysterectomy (OR: 2.43, 95%CI 1.69–3.50). However, none of the associations were statistically significant (Hysterectomy: OR: 1.21, 95%CI 0.8–1.85; Menopause: OR: 1.43, 95%CI 0.88–2.31; TL: OR: 1.01, 95%CI 0.74–1.37) in the fully adjusted model (after adjustment for age, diabetes, hypertension, residential area, waist-to-hip ratio, pregnancy number, socio-economic state, occupation, education, and physical activity). Although some models showed significance, none of the reproductive factors showed a significant association with CHD after full adjustment.